PENGARUH DOSIS KOMPOS TONGKOL JAGUNG TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum (L.)) - Akhmad Zulmy Assiddiqi; Sulistyawati Sulistyawati; Retno Tri Purnamasari; Fajar Hidayanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
This study aims to determine the effect of the dose of corncob compost on the growth and production of shallots. The research was conducted in Pateguhan Village, Pasuruan Regency from January to April 2021. The soil used had a pH of 5.8 with a c-organic content of 2.41%, N-total 0.17%, P2O5 38.46 ppm, and K2O 0.80 ppm. This study was arranged in a one-factor randomized block design (RBD) with six replicates with the following treatment with doses of corncob compost: P0 = control, without corncob composting P1 = treatment with compost at a dose of 10 tons.ha-1 P2 = treatment giving compost at a dose of 15 tons.ha-1 P3 = treatment with compost at a dose of 20 tons.ha-1. The data obtained from the study were analyzed using analysis of variance (F test), if there was a significant effect, then continued with the 5% level BNT test. The results showed that the dose of corncob compost treatment had an effect on the growth and yield of shallots. Treatment of corn cobs compost at a dose of 20 tons.ha-1 gave the highest yield on the observation of growth components, growth analysis and yield components. Treatment of corncob compost at a dose of 20 tons.ha-1 produced a tuber weight of 8.74 tons.ha-1, at a dose of 15 tons.ha-1 corn cobs compost treatment produced a tuber weight of 6.49 tons.ha-1, at a dose of 10 ton.ha-1 corn cobs compost treatment yielded tuber weight of 5.26 ton.ha-1 and the lowest yield was found in the control treatment with yield of 4.17 ton.ha-1.